KEMAMPUAN MENULIS AKADEMIK GURU MATA PELAJARAN NON-BAHASA DI JAWA BARAT - Setiadi, Riswanda (LITERA, 2016)
This study aims to: (a) assess the academic writing skills of non-language teachers, (b) analyze mistakes in their academic writing test results, and (c) identify factors causing the difficulties they encounter in developing their academic writing skills. The subjects were 126 non-language teachers who had participated in the teacher certification program from 14 regencies/cities in West Java Province. The findings show that on the whole their academic writing mean score is 57.2 of a total score of 100. Referring to an academic writing assessment scale, the mean score is fairly good. Writing experiences, training, and academic atmosphere are important factors that have contributions to teachers’ academic writing skills.